Australian Muslim women and fitness choices – myths debunked. Issue 5 (14th June 2018) - Summers, Jane; Hassan, Rumman; Ong, Derek; Hossain, Munir
Abstract : Purpose: The purpose of this paper was to better understand the underrepresentation of Muslim women living in Australia in physical activity and in group-fitness classes in particular. The authors contend that the Australian fitness industry has ignored the needs of this group through stereotypical islamophobic views focusing on religious dictates as the prime barrier for participation of this group. This study debunks this myth showing that motivations for exercise are complex and multi-faceted. Design/methodology/approach: The authors conducted interviews and a focus group with 27 Muslim women living in Australia. Through this method, the authors explored the role of religiosity and national culture in attitudes towards participation in exercise, gym attendance and group fitness classes. Findings: The authors confirmed that while religion impacted the form and place of exercise options, it did not impact the overall motivation to engage in exercise. This study found that group-fitness classes offered by gyms did not particularly appeal to this group of women, partially due to their religion (this form of exercise being too aggressive and immodest) and partially due to their ethnic background. Exercise options that were more social were favoured. The authors found that notions of femininity and culturally embedded expectations for the role of women were more powerful predictors of exercise engagement and choice of exercise type. Research limitations/implications: This research is exploratory in nature and as such its findings are restricted to the small sample. To extend this study's implications, a larger empirical study should be conducted and needs to also consider the intersection between national culture and religiosity on decision-making. Practical implications: This study has practical implications for the fitness industry attempting to attractive new markets in a multi-cultural population. To attract Muslim women, gyms and fitness centres need to consider providing appropriate areas for women to exercise that allow them to maintain their modesty. To attract this segment, fitness products that are focused on a holistic approach to wellness and highlight opportunities for social interaction should be developed. Focusing on this group as a market segment needs to include a broader contextualisation of their lifestyles and individual situations and should not just focus on their religion. Social implications: The requirements of the Muslim religion for women to adopt conservative dress and to avoid contact with men do hinder their ability and also their desire to exercise to maintain a healthy mind and body. Many of these women would like to exercise but find it difficult to find the right settings and form of exercise that suits their needs. Engaging in exercise with others is also an important way for these women to integrate into their communities and to assimilate with the national culture. Originality/value: This research is original in that it is one of the first to explore attitudes of Muslim women towards exercise and group-fitness classes in Australia. In particular, it includes an examination of the impact of religiosity on motivations and attitudes towards fitness and is the first to consider the relationship between religion, ethnic background and notions of femininity in the context of fitness. The influence of religiosity is an area heavily impacted by cultural bias and stereotyping, and it is therefore important for a deeper understanding of this issue in the services domain.